IMPLEMENTASI SISTEM MONITORING JARINGAN INTERNAL MENGGUNAKAN UPTIME KUMA YANG TERINTEGRASI DENGAN BOT TELEGRAM DI PT BENTANG JOHAR AWAL - Nugraha, Nugraha; Saffira, Allya (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Network stability is a crucial aspect in supporting the smooth operation of a company. However, many companies still do not have a network monitoring system that can provide automatic notifications when disruptions occur. This community service activity aims to assist partners in implementing an internal network monitoring system based on Uptime Kuma, integrated with a Telegram Bot, to enhance responsiveness to service disruptions. The method used is a participatory applicative approach, with stages of partner needs identification, system monitoring implementation, and system testing. Through the Uptime Kuma dashboard, the network devices to be monitored are manually added by the user. The devices are configured using a ping-based monitoring method, with a check interval of 60 seconds. The test results show that the system is able to detect changes in device status in real-time and send automatic notifications to Telegram without delay. All trials, whether when the device is down or up, were detected consistently and accurately. Thus, the implementation of this system has proven to be effective and efficient in improving the reliability of monitoring the company's IT infrastructure.